The effect of electrolyte parameter variation upon the performance of lithium iron phosphate (LiFePO4) - Ranom, Rahifa; Ahmad Jamal, Saidatul Nur Aisyahtun Sakinah; Bacho, Risna Syakinah (Institute of Advanced Engineering and Science, 2022)
This study focuses on the effect of electrolyte parameter variation upon the performance of lithium iron phosphate (LiFePO4) due to high demand of the electronic devices among consumers and industrial sectors that require efficicent LiFePO4 batteries. Hence, it is essential to improve its performance by optimizing the electrolyte parameter of the cell. The mathematical models of lithium-ion batteries based on the drift-diffusion model consists of the electrolyte and lithium transport equations in the electrode particles which incorporated the geometry of cell microstructure to the coefficients in the macroscopic model was solved numerically using the method of lines (MOL) technique. The effect of electrolyte parameter variation on the discharge curve of LiFePO4 using lithium hexa-fluorophosphate (LiPF6 ) as the base electrolyte is examined by varying the electrolyte parameters: initial concentration of lithium ions (c0), the effective diffusivity of lithium ions (D) and the effective ionic conductivity (